Advances in Environmental Remote Sensing - Weng, Quihao (CRC Press, 2012)
Featuring contributors from 17 countries, this book systematically presents recent advances in environmental remote sensing. First, the text provides the latest developments in remote sensing data and sensor systems, paying special attention to LIDAR, high spatial-resolution sensing, hyperspectral sensing, and data fusion of various sensors